Deciphering the origins of the elements through galactic archeology - Farouqi, Khalil; Frebel, Anna; Thielemann, Friedrich-Karl (The European physical journal. A, Hadrons and nuclei, 2025)
Low-metallicity stars preserve the signatures of the first stellar nucleosynthesis events in the Galaxy, as their surface abundances reflect the composition of the interstellar medium from the time when they were born. Aside from primordial Big Bang nucleosynthesis, massive stars, due to their short lifetimes, dominate the wind and explosive ejecta into the interstellar medium of the early Galaxy. Most of them will end as core-collapse supernova (CCSN) explosions, and typical ejected abundance distributions, e.g. in terms of the $$α $$-element-to-Fe ratios, reflect these contributions. Essentially all CCSNe contribute 56Fe (decaying from radioactive 56Ni). Therefore, low-metallicity stars can be used to test whether the abundances of any other elements are correlated with those of Fe, i.e. whether these elements have been co-produced in the progenitor sources or if they require either a different or additional astrophysical origin(s). The present analysis focuses on stars with [Fe/H]<-2, as they probe the earliest formation phase of the Galaxy when only one or very few nucleosynthesis events had contributed their ejecta to the gas from which the lowest metallicity stars form. This was also the era before low and intermediate mass stars (or type Ia supernovae) could contribute any additional heavy elements. Following earlier work on the origin of heavy r-process elements [1], we extend the present study to examine Pearson and Spearman correlations of Fe with Li, Be, C, N, O, Na, Mg, Si, S, K, Ca, Ti, Cr, Ni, Zn, Ge, Se, Sr, Y, Zr, Mo, Ba, La, Ce, Sm, Eu, Gd, Dy, Yb, Lu, Hf, Os, Ir, Pb, and Th, using high-resolution stellar abundance data from the SAGA [2] and JINA [3] databases. The main goal is to identify which of the observed elements (i) may have been co-produced with Fe in (possibly a variety of) CCSNe, and which elements require (ii) either a completely different, or (iii) at least an additional astrophysical origin.
Gesehen am 29.01.2026